2005
DOI: 10.1136/pgmj.2004.030148
|View full text |Cite
|
Sign up to set email alerts
|

The laparoscopic nephrectomy learning curve: a single centre’s development of a de novo practice

Abstract: Objective: There has been a dramatic increase in the interest and practice of laparoscopic urology, with nephrectomy having become the commonest laparoscopic urological procedure. Compared with open nephrectomy, it results in reduced morbidity and shorter convalescence times while maintaining oncological safety. However, while these results predominately stem from institutions with well developed laparoscopic programmes, little is known about the results in centres that have newly adopted this technique. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…It is quite evident that operative time is not the main determinative criterion for the learning curve. However, operative times shorten or even remain stable after an increase in the number of cases ( 11 ). In their series of 100 cases with laparoscopic nephrectomies, Gill et al estimated mean operative times as 175, and 163 minutes for the first, and the next 50 cases of their series ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is quite evident that operative time is not the main determinative criterion for the learning curve. However, operative times shorten or even remain stable after an increase in the number of cases ( 11 ). In their series of 100 cases with laparoscopic nephrectomies, Gill et al estimated mean operative times as 175, and 163 minutes for the first, and the next 50 cases of their series ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies have examined the LC of surgical trainees learning LDN , no study to date has comprehensively examined the multimodal metrics of the operation in a single analysis. These studies confirm the inverse relationship between surgeon experience and operative time and the indirect extrapolation to surgical proficiency; however, training and teaching laparoscopic skills involves complex surgical decision making and a rapidly changing intraoperative dynamic that involve a broad set of metrics.…”
Section: Discussionmentioning
confidence: 99%
“…It is true, however, that the operative time decreases as the number of cases performed increases, and at some point the decline comes to a halt. [12][13][14] Therefore, it is plausible to consider the operative time as one of several significant indicators of the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…The number of surgical cases needed to overcome this learning curve is controversial. Phillips and colleagues 13 reported that operative time did not decrease further after the first 20 cases; therefore, it was concluded that the learning curve for laparoscopic nephrectomy was approximately 20 cases. The subjected disease, however, was a different one.…”
Section: Discussionmentioning
confidence: 99%